Impacts of fertilization methods on Salvia miltiorrhiza quality and characteristics of the epiphytic microbial community - Gong, Feng; He, Chao; Li, Xianen; Wang, Kehan; Li, Min; Zhou, Xiangyun; Xu, Minghui; He, Xueli (Frontiers in Plant Science, 2024)
Plant epiphytic microorganisms have established a unique symbiotic relationship with plants, which has a significant impact on their growth, immune defense, and environmental adaptation. However, the impact of fertilization methods on the epiphytic microbial community and their correlation with the yield and quality of traditional Chinese medicine are still unclear.In current study, we conducted a field fertilization experiment and analyzed the composition of epiphytic bacterial and fungal communities employing high throughput sequencing data in different organs (roots, stems, leaves) of Salvia miltiorrhiza plants, as well as their correlation with plant growth. The results showed that fertilization significantly affected the active ingredients and hormone content, soil physicochemical properties, and the composition of epiphytic microbial communities. After fertilization, the surface of the plant was enriched with a core microbial community mainly composed of bacteria from Firmicutes, Proteobacteria, and Actinobacteria, as well as fungi from Zygomycota and Ascomycota. Additionally, plant growth hormones are the principal factors leading to alterations in the epiphytic microbial community of S. miltiorrhiza. Thus, the most effective method of fertilization involved the application of base fertilizer in combination with foliar fertilizer. This study offers a novel perspective on the correlation between microbial community function and the quality of S. miltiorrhiza. Moreover, our data also provides a theoretical foundation for the cultivation of high-quality traditional Chinese medicinal materials and their sustainable development.